Reconceptualizing islamic counseling for global mental health: An integrative framework - Kholilurrohman Kholilurrohman; Abdul Mufid; Mowafg Abrahem Masuwd; Kauthar Razali (Jurnal Ilmu Dakwah, 2026)
Purpose – The study aims to reconceptualize Islamic counseling by developing an integrative framework that contributes to the global mental health discourse. Specifically, it seeks to answer how Islamic counseling can be theoretically integrated with global mental health and evidence-based counseling approaches to promote psychological wellbeing and resilience among Muslim populations. Method – The study utilizes a conceptual and integrative literature review method, focusing on synthesizing key insights from global mental health literature, evidence-based counseling practices, and Islamic counseling principles. Relevant peer-reviewed international publications, policy reports, and theoretical models were systematically analyzed to identify conceptual intersections, highlight key findings, and address existing gaps in the literature. Result – The findings propose an Integrative Islamic counseling framework that bridges Islamic spiritual principles (such as meaning-making, self-regulation, resilience, and adaptive acceptance) with contemporary global mental health paradigms and evidence-based counseling practices. The framework positions Islamic counseling as a culturally responsive and complementary approach that enhances psychological wellbeing, resilience, and mental health promotion without opposing established clinical methods. Implication – This study has significant implications for both global mental health practices and the integration of Islamic principles into mainstream counseling. It provides a culturally relevant model for addressing mental health issues within Muslim communities and highlights the importance of incorporating diverse cultural and spiritual perspectives into psychological care, fostering resilience and psychological wellbeing. Originality/Value – The originality of this study lies in its proposal of an Integrative Islamic Counseling Framework, which is an underexplored area in the field of global mental health. *** Tujuan – Studi ini bertujuan untuk merekonseptualisasi konseling Islami dengan mengembangkan kerangka kerja integratif yang berkontribusi pada wacana kesehatan mental global. Secara khusus, studi ini berupaya menjawab bagaimana konseling Islami dapat diintegrasikan secara teoritis dengan kesehatan mental global dan pendekatan konseling berbasis bukti untuk meningkatkan kesejahteraan psikologis dan ketahanan di kalangan populasi Muslim. Metode – Studi ini menggunakan metode tinjauan literatur konseptual dan integratif. Studi ini mensintesis wawasan utama dari literatur kesehatan mental global, praktik konseling berbasis bukti, dan prinsip-prinsip konseling Islami. Publikasi internasional yang relevan dan telah ditinjau oleh rekan sejawat, laporan kebijakan, dan model teoretis dianalisis secara sistematis untuk mengidentifikasi persimpangan dan kesenjangan konseptual. Hasil – Temuan ini mengusulkan Kerangka Kerja Konseling Islami Integratif yang menjembatani prinsip-prinsip spiritual Islam (seperti penciptaan makna, pengaturan diri, ketahanan, dan penerimaan adaptif) dengan paradigma kesehatan mental global kontemporer dan praktik konseling berbasis bukti. Kerangka kerja ini memposisikan konseling Islami sebagai pendekatan yang responsif secara budaya dan komplementer yang meningkatkan kesejahteraan psikologis, ketahanan, dan promosi kesehatan mental tanpa bertentangan dengan metode klinis yang sudah mapan. Implikasi – Studi ini memiliki implikasi signifikan baik untuk praktik kesehatan mental global maupun integrasi prinsip-prinsip Islam ke dalam konseling arus utama. Studi ini menyediakan model yang relevan secara budaya untuk mengatasi masalah kesehatan mental dalam komunitas Muslim dan menyoroti pentingnya memasukkan beragam perspektif budaya dan spiritual ke dalam perawatan psikologis, menumbuhkan ketahanan dan kesejahteraan psikologis. Orisinalitas/Nilai – Orisinalitas studi ini terletak pada usulannya tentang Kerangka Konseling Islam Integratif, yang merupakan area yang kurang dieksplorasi dalam bidang kesehatan mental global.